Of Anonymity and Attribution and the Challenges of Controlling Cybercrime in South Africa - Oladejo, Abiodun Omotayo; Dastile, Nontyatyambo Pearl (Acta Universitatis Danubius. Juridica, 2025)
The advent of the digital age has considerably changed the way we live because of the pervasiveness of human-technology interface. While the myriads of cyber technologies have enhanced the human world, they have also produced undesirable consequences, the major of which is cybercrime. In South Africa, cybercrime is fast becoming an endemic issue, affecting businesses, individuals, and the public sector. The usual narratives about cybercrime control have centred more on the legislative and institutional frameworks rather than the nature of the crime, which is largely intangible. This paper, relying on critical review technique, foregrounds anonymity and attribution as critical factors impeding the effectiveness of cybercrime prosecution. To circumnavigate these challenges, we advocate for improved investigative and cyberspace knowledge (such as the state-of-the-art digital forensics) for the South African Police Service and collaboration with private cybersecurity and computer technology companies. Although difficult given the rapid pace of technological development, these are necessary steps if there will be a rise in the effectiveness of cybercrime control in South Africa.